2012
DOI: 10.1615/critrevbiomedeng.v40.i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Motion Compensation Strategies in Magnetic Resonance Imaging

Abstract: Image quality in magnetic resonance imaging (MRI) is considerably affected by motion. Therefore, motion is one of the most common sources of artifacts in contemporary cardiovascular MRI. Such artifacts in turn may easily lead to misinterpretations in the images and a subsequent loss in diagnostic quality. Hence, there is considerable research interest in strategies that help to overcome these limitations at minimal cost in time, spatial resolution, temporal resolution, and signal-to-noise ratio. This review su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 119 publications
1
61
0
Order By: Relevance
“…Motion artifacts can be mitigated using breath-hold acquisition in cooperative subjects, or by navigator or breathing-belt triggering in the others [21]. Recently, Robson et al [22] showed that the combined use of techniques of background suppression (which use multiple RF inversion pulses to suppress signals from the static tissue) and breathing strategies improves the repeatability of perfusion measurements over the kidneys.…”
Section: Renal Asl Mri In Healthy Volunteersmentioning
confidence: 99%
“…Motion artifacts can be mitigated using breath-hold acquisition in cooperative subjects, or by navigator or breathing-belt triggering in the others [21]. Recently, Robson et al [22] showed that the combined use of techniques of background suppression (which use multiple RF inversion pulses to suppress signals from the static tissue) and breathing strategies improves the repeatability of perfusion measurements over the kidneys.…”
Section: Renal Asl Mri In Healthy Volunteersmentioning
confidence: 99%
“…Self-gated MRI corrects motion artifacts based on MRI signal intensity variations (19). Despite being less sensitive to the earlier stages of lung inflammation, this technique has been proven to provide more accurate information in visualizing and quantifying the progression of lung fibrosis in BLM-treated mice (20).…”
Section: Proton Mrimentioning
confidence: 99%
“…However, these approaches reduce data sampling efficiency and generally result in prolonged imaging times. To retain scan efficiency and still reduce the effects of respiratory motion artifacts without breath-holding, several groups [5] have explored rapid continuous free-breathing MRI radial acquisition schemes with compressed sensing reconstruction, for several types of MRI (including cardiac, as well as liver and brain MRI) [68]. However, those studies have primarily focused on providing a proof-of-concept demonstration of the feasibility of the proposed imaging strategy.…”
Section: Introductionmentioning
confidence: 99%